2014
DOI: 10.1007/7854_2014_342
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brain Lesions on Moral Agency: Ethical Dilemmas in Investigating Moral Behavior

Abstract: Understanding how the "brain produces behavior" is a guiding idea in neuroscience. It is thus of no surprise that establishing an interrelation between brain pathology and antisocial behavior has a long history in brain research. However, interrelating the brain with moral agency-the ability to act in reference to right and wrong-is tricky with respect to therapy and rehabilitation of patients affected by brain lesions. In this contribution, we outline the complexity of the relationship between the brain and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 78 publications
0
3
0
5
Order By: Relevance
“…关于道德行为和脑功能定位, 前者涉及多种道德 能力, 后者指与心理功能相联系的特定大脑网络结 构 [8] . 道德行为指与善恶观念相联系的活动, 包括善行 和恶行, 即道德的行为和不道德的行为 [9,10] .…”
Section: 道德行为和脑功能定位的关系概述unclassified
See 2 more Smart Citations
“…关于道德行为和脑功能定位, 前者涉及多种道德 能力, 后者指与心理功能相联系的特定大脑网络结 构 [8] . 道德行为指与善恶观念相联系的活动, 包括善行 和恶行, 即道德的行为和不道德的行为 [9,10] .…”
Section: 道德行为和脑功能定位的关系概述unclassified
“…对道德情境中的消极情绪敏感. Roberts等人 [14] 基于脑 损伤的综述性研究认为, 可能造成不道德行为的脑区 损伤包括杏仁核、前扣带回、额下回、眶额叶、后侧 颞上沟、颞顶连接处、腹内侧前额叶、前脑岛等的损 伤. Christen和Müller [8] 认为, 直接参与不道德行为的皮 层结构主要有右侧眶额叶和右侧腹内侧前额叶, 皮下 结构主要有杏仁核、海马和基底核. 关于特定不道德 行为有研究者认为, 与暴力行为有关的脑区损伤包括 额叶、左侧边缘系统、小脑扁桃体、脑岛等的损伤以 及胎儿期药物滥用导致的全脑损伤、问题养育环境导 致的注意力失调有关的脑区损伤等 [18] .…”
Section: 道德行为和脑功能定位的关系概述unclassified
See 1 more Smart Citation
“…10 Examples of persons whose capacity is reduced due to non-cognitive factors are persons suffering from major depression, anorexia nervosa, 11 drug addiction, 12 body dysmorphic disorder, body integrity identity disorder, 13 or acquired psychopathy (Phineas Gage type). 14 The question of which non-cognitive factors can reduce the capacity for autonomy is being currently discussed intensively by German psychiatrists and legal theorists. The ethics task force of the German Association for Psychiatry, Psychotherapy and Psychosomatics (DGPPN) stated that psychiatric disorders could influence the different components of self-determination in different ways.…”
Section: Shortcomings Of Beauchamp and Childress' Concept Of Autonomymentioning
confidence: 99%
“…In addition, various studies have suggested that it might be possible to use neuroscientific evidence to establish the decisionmaking capacity of individuals with pathologies which affect moral reasoning and behaviour. 88 Finally, there has been considerable debate within ethics itself about the potential normative significance to settle issues of practical ethics. This debate is influenced by the pre-existing and more general challenges raised by experimental philosophy against traditional armchair methods of doing philosophy and ethics.…”
Section: Knowledge Transfer To Whom?mentioning
confidence: 99%